Subjective Study on Pediatric Emergency Department Nurses' Perceptions of Urgency Using Q Methodology - Hyeyeon Yeon; Sunhui Choi; Danbi Park; Min Jeong Seo (Elsevier, 2024)
Summary: Purpose: In the emergency department (ED), triage significantly impacts patient safety. Therefore, triage nurses must make decisions accurately and timeously. This study aims to investigate how South Korean pediatric emergency nurses perceive urgency and classify severity using the Q methodology, which examines individuals' subjectivity. Methods: We collected 84 statements from a Q population based on a literature review and interviews and selected 33 Q samples. The P samples included 30 pediatric emergency nurses at a Seoul tertiary care hospital. The principal component factor analysis method was used to analyze data using the PC-QUANL program. Results: Four urgency perception types were identified among pediatric ED nurses-Type 1: "Experiential coping"; Type 2: "Careful reasoning"; Type 3: "Patient-centered thinking"; and Type 4: "Intuitive prediction." These types appear to be an integrated process of knowledge and clinical experience that considers children's characteristics and developmental stages. Conclusion: This study may serve as a basis for future education to improve pediatric ED nurses' urgency judgment and severity classification skills.